Is less always more? A prospective two-centre study addressing clinical outcomes in leadless versus transvenous single-chamber pacemaker recipients. (3rd October 2022) - Bertelli, M; Toniolo, S; Gasperetti, A; Schiavone, M; Arosio, R; Statuto, G; Ziacchi, M; Mitacchione, G; Angeletti, A; Spadotto, A; Bartoli, L; Lazzeri, M; et al.
Abstract: Background: Transvenous (TV) pacemakers are a well established treatment of bradyarrhythmias yet their complications, namely bleeding, infection and pneumothorax, still pose challenges to modern cardiology. This applies particularly to the older patient subgroup requiring single-chamber pacing due to comorbid atrial fibrillation (AF). Furthermore, conditions such as superior venous access issues, high infectious, or bleeding risk may complicate or preclude transvenous lead implantation. While VVIR leadless (LL) pacemakers aim to tackle these shortcomings, a comparison with contemporary single-chamber TV cohorts is currently lacking thus hindering a clear definition of the scope of LL pacing in clinical practice. Purpose: To prospectively analyse survival and complication rates in leadless versus transvenous single-chamber pacemaker recipients. Methods: This is a prospective analysis of 344 consecutive patients who received single-chamber TV or LL pacemakers between June 2015 and May 2021 in two tertiary cardiology centres. Indications for single-chamber pacing were "slow" AF, atrio-ventricular block with comorbid AF (either permanent or accepted as "destination rhythm") or with sinus rhythm in bedridden cognitively impaired patients. LL indications were ongoing or expected chronic haemodialysis (6.9%), superior venous access issues such as occlusion (11.1%) or need for its preservation (9.7%), active lifestyle with low amount of pacing expected (22.2%), frailty causing high bleeding and infectious risk (23.6%), as well as recent valvular endocarditis (2.8%) or implantable electronic device infection requiring extraction (5.6%). Results: 72 patients (20.9%) received LL and 272 (79.1%) TV single-chamber pacemakers. In keeping with LL indications, diabetes and ongoing haemodialysis were more prevalent in the LL population. No significant difference in overall complication rate was observed between LL and TV patients (5.6% vs. 5.1%, p=0.33) apart from haematomas, which occurred more frequently in the LL population. Only 1 haematoma in the TV group required surgical reintervention. TV recipients survival was lower with greater cardiovascular mortality, likely due to selection of significantly older patients. Conclusions: Given the limited complication rate observed in this contemporary single-chamber TV cohort and low life expectancy of this particular population, extending LL indications to all VVIR candidates is unlikely to provide a clearcut survival advantage. Considering the higher costs of LL technology, these data prompt a careful selection of those cases where LL approach does indeed provide an advantage. In addition to the setting of vascular access issues and high bleeding or infectious risk, these may include patients with sufficient life expectancy where lead-related risks may indeed adversely affect prognosis. Based on our patient selection criteria, LL might account for approximately 20% of VVIR pacing recipients. Funding Acknowledgement: Type of funding sources: None.